θ
=∫√(2GMv02r0-v04r02)/[GM+(GM-v02r0)cosφ] *dφ
=∫√(v04r02-2GMv02r0)/[GM+(GM-v02r0)coshψ] *dψ
=√(2GMv02r0-v04r02)∫dφ[cos²(φ/2)+sin²(φ/2)]/[(2GM-v02r0)cos²(φ/2)+v02r0sin²(φ/2)]
=√(v04r02-2GMv02r0)∫dψ[cosh²(ψ/2)-sinh²(ψ/2)]/[(2GM-v02r0)cosh²(ψ/2)-v02r0sinh²(ψ/2)]
=2√(2GMv02r0-v04r02)∫d(φ/2)[1+tan²(φ/2)]/[2GM-v02r0+v02r0tan²(φ/2)]
=2√(v04r02-2GMv02r0)∫d(ψ/2)[1-tanh²(ψ/2)]/[2GM-v02r0-v02r0tanh²(ψ/2)]
=2/(2GM-v02r0)*√(2GMv02r0-v04r02)∫d(φ/2)sec²(φ/2)/[1+v02r0/(2GM-v02r0)*tan²(φ/2)]
=2/(2GM-v02r0)*√(v04r02-2GMv02r0)∫d(ψ/2)sech²(ψ/2)/[1-v02r0/(2GM-v02r0)*tanh²(ψ/2)]
=2/√(2GMv02r0-v04r2)*√(2GMv02r0-v04r02)∫d(φ/2)√[v02r0/(2GM-v02r0)]sec²(φ/2)/[1+v02r0/(2GM-v02r0)*tan²(φ/2)]
=2/√(v04r2-2GMv02r0)*√(v04r02-2GMv02r0)∫d(ψ/2)√[v02r0/(v02r0-2GM)]sech²(ψ/2)/[1+v02r0/(v02r0-2GM)*tanh²(ψ/2)]
=2∫d{√[v02r0/(2GM-v02r0)]tan(φ/2)}/{1+[√[v02r0/(2GM-v02r0)]tan(φ/2)]^2}
=2∫d{√[v02r0/(v02r0-2GM)]tanh(ψ/2)}/{1+[√[v02r0/(v02r0-2GM)]tanh(ψ/2)]^2}
=2arctan{√[v02r0/(2GM-v02r0)]tanφ/2} + constC
=2arctan{√[v02r0/(v02r0-2GM)]tanhψ/2} + constC
∵θ(0)=0,φ(0)=0,ψ(0)=0,constC=constD=0
tan(θ/2)=
√[v02r0/(2GM-v02r0)]tan(φ/2)
√[v02r0/(v02r0-2GM)]tanh(ψ/2)